1981
DOI: 10.1128/jb.145.2.681-686.1981
|View full text |Cite
|
Sign up to set email alerts
|

Properties of six pesticide degradation plasmids isolated from Alcaligenes paradoxus and Alcaligenes eutrophus

Abstract: Biophysical and genetic properties of six independently isolated plasmids encoding the degradation of the herbicides 2,4-dichlorophenoxyacetic acid and 4chloro-2-methylphenoxyacetic acid are described. Four of the plasmids, pJP3, pJP4, pJP5, and pJP7, had molecular masses of 51 megadaltons, belonged to the IncPl incompatibility group, and transferred freely to strains of Escherichia coli, Rhodopseudomonas sphaeroides, Rhizobium sp., Agrobacterium tumefaciens, Pseudomonas putida, Pseudomonas fluorescens, and Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
1
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(204 citation statements)
references
References 23 publications
4
198
1
1
Order By: Relevance
“…Likewise, in one of Âąve well-known phenol degraders the acquisition of pRO103 did not result in the ability to degrade PAA. Other studies have found that catabolic genes when present in some host strains are not always properly expressed [8,11,30]. This could be due to e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, in one of Âąve well-known phenol degraders the acquisition of pRO103 did not result in the ability to degrade PAA. Other studies have found that catabolic genes when present in some host strains are not always properly expressed [8,11,30]. This could be due to e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The involvement of plasmids in the degradation of 2,4-D was first demonstrated by Pemberton and co-workers in Alcaligenes paradoxus strain JMPll6, which contained the plasmid pJP1 [156,369]. Several indistinguishable plasmids, which encoded the degradation of 2,4-D and MCPA, were later isolated from strains of A. paradoxus and A. eutrophus [158,370]. Plasmids encoding the degradation of 2,4-D have been found in numerous other bacteria as well [159,161,162].…”
Section: Genetic Basis Of Degradation and Construction Of Novel Strainsmentioning
confidence: 94%
“…[52] and in Alcaligenes sp. [53]. Genes for CO metabolism are located on a 128-kb endogenous plasmid in Pseudomonas carboxydovorans OM5 [541.…”
Section: The Possible Role Of Endogenous Plasmids In Carbon and Nitromentioning
confidence: 99%